The Evaluation Forms of International Passenger Airport Hub in Southeast Asia - Jantachalobon, Nattapong; Suthikarnnarunai, Nanthi (Journal of Applied Engineering Science, 2015)
This research aims to present the selection of Asean international airports in order to establish the international passenger airport hub in Southeast Asia. The study focused on the airports in Southeast Asia region which most passengers travelling through as follows : Singapore’s Changi International Airport (SIN),Cambodia’s Phnom Pehn International Airport (PNH),Brunei’s Brunei international Airport (BWN), Indonesia’s Sugarno Hatta International Airport (CGK), Lao PDR’s Wattay International Airport (VTE), Malaysia’s Kuala Lumpur International Airport (KUL), Myanmar’s Rangoon International Airport (RGN), the Philippines’ Ninoy Aquino International Airport (MNL), Thailand’s Suvarnabhumi International Airport (BKK), and Vietnam’s Tan Son Nhat International Airport (SGN) as the optional airports. In order to acquire the most suitable areas in the engineering perspective, the Multiple Criteria Decision Making (MCDM) has been applied by using both Technique for Order Preference by Similarity to Ideal Solution-TOPSIS and Analytic Hierachy Process-AHP. There are 5 main criterions to be considered consisting of Geographical factors, Economic Factors, Functional Factors, Operational Factors and other factors. The two main research methodology to gain these factors which effecting the establishment of airport hubs consist of Delphi method and Regression analysis. The research will be the benefits for managing airports and developing their airport hub. Moreover the study of the research will be useful for Southeast Asia governments to determine the relevant policies and planning for aviation business development of the country.